LoRa Mobile-To-Base-Station Channel Characterization in the Antarctic - Johnny Gaelens; Patrick Van Torre; Jo Verhaevert; Hendrik Rogier (Sensors, 2017)
Antarctic conditions demand that wireless sensor nodes are operational all year round and that they provide a large communication range of several tens of kilometers. LoRa technology operating in sub-GHz frequency bands implements these wireless links with minimal power consumption. The employed chirp spread spectrum modulation provides a large link budget, combined with the excellent radio-wave propagation characteristics in these bands. In this paper, an experimental wireless link from a mobile vehicle which transmits sensor data to a base station is measured and analyzed in terms of signal-to-noise ratio and packet loss. These measurements confirm the usefulness of LoRa technology for wireless sensor systems in polar regions. By deploying directional antennas at the base station, a range of up to 30 km is covered in case of Line-of-Sight radio propagation in both the 434 and 868 MHz bands. Varying terrain elevation is shown to be the dominating factor influencing the propagation, sometimes causing the Line-of-Sight path to be obstructed. Tropospheric radio propagation effects were not apparent in the measurements.